2010
DOI: 10.1364/oe.18.015790
|View full text |Cite
|
Sign up to set email alerts
|

Efficient planar fiber-to-chip coupler based on two-stage adiabatic evolution

Abstract: A new, efficient adiabatic in-plane fiber-to-chip coupler design is proposed. In this design, the light from the fiber is coupled into a low-index waveguide with matching mode size. The mode is first adiabatically reduced in size with a rib taper, and then transferred into a high-index (e.g. silicon) waveguide with an inverse taper. The two-stage design allows to reduce the coupler length multiple times in comparison with pure inverse taper-based couplers of similar efficiency. The magnitude of length reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…An error of only 1 nm in the average waveguide width produces indeed a shift of the ring resonance of about 125 GHz [65]. Moreover, with state-of-theart SOI technology, silicon nanometric waveguides exhibit propagation losses of about 1-2 dB/cm [117] and a challenging fiber-to-waveguide coupling that can be reduced down to 1-2 dB/facet only by means of complex mode-adapting structures [118][119][120].…”
Section: Soi Technologymentioning
confidence: 99%
“…An error of only 1 nm in the average waveguide width produces indeed a shift of the ring resonance of about 125 GHz [65]. Moreover, with state-of-theart SOI technology, silicon nanometric waveguides exhibit propagation losses of about 1-2 dB/cm [117] and a challenging fiber-to-waveguide coupling that can be reduced down to 1-2 dB/facet only by means of complex mode-adapting structures [118][119][120].…”
Section: Soi Technologymentioning
confidence: 99%
“…The injector waveguide comprises a 3.5-µm-thick layer of siliconrich oxide with a specific refractive index by controlling the amount of silicon nanocrystals. Khilo et al 15 reported a coupler based on combination of rib and inverse tapers. First, the light is coupled into a low-index rib waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…First, its compliant aspect mechanically decouples the chip optical interface from cycling strains in the package, which is expected to significantly improve long-term reliability when compared to solutions employing rigid interfaces or direct fiber to chip [3][4]. Second, its optical bandwidth can be very large.…”
Section: Introductionmentioning
confidence: 99%